O poder simbólico e a invenção das tradições no patrimônio cultural: estudo dos usos turísticos na Fazenda do Pontal em Itabira (MG) - Luciana Santos Ferreira (2019)
Cultural heritage is connected to society through its symbols and some traditions of a place and its time. From the concepts of invented tradition (Hobsbawm and Ranger, 1997) and symbolic power (Bourdieu, 1989), it is intended to contextualize Pontal Farm historically, located in Itabira (MG), with its rural architecture and its social insertion. The symbolic influence of the figure of Carlos Drummond de Andrade (19021987) was one of the ways for establishing this cultural achievement. It was intended to investigate the actions promoted by the municipal institutions related to Pontal Farm and whether such initiatives contributed to the adherence of this element of cultural heritage in the social imaginary of the local community and tourists. The research methodology was based on bibliographical analysis in the field of cultural heritage in the historical and social senses, along with documentary research using primary sources found in the public archives of Minas Gerais, as well as the consultation on Drummond’s literary production related to the referred place. It was also carried out an observatory field research and semi-structured interviews. It is concluded that the new representation of Pontal Farm is an element of cultural heritage, built from a symbolic manipulation that penetrated the social imaginary through repetitive rites as a practice of an invented tradition for tourist purposes and from the community that intended to dissociate itself from the mining exploration image of the region.